FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN IMPLEMENTASI SISTEM ENTERPRISE RESOURCE PLANNING PERSEDIAAN (STUDI KASUS PT API) - Wijaya, Muhamad Rizky; Maylindasari, Maylindasari; Pratama, Ifanny Adnan (JUBISMA, 2024)
This research aims to analyze the factors that influence the successful implementation of the inventory Enterprise Resource Planning (ERP) system at PT Amanah Prima Indonesia. The factors described include top management support, user involvement and training and education. The research method used was quantitative through a questionnaire distributed to 35 respondents who used the Inventory ERP system. The analysis assistance technique used is multiple linear regression with SPSS version 27 software. The research results show that simultaneously the factors of top management support, user involvement and training and education have a significant effect on the success of implementing the inventory ERP system at PT Amanah Prima Indonesia by 81.1%. However, partially only the user involvement factor has a significant effect on the success of implementation, while top management support factors and training and education factors do not have a significant effect. These findings demonstrate the important role of active user involvement in increasing the success of inventory ERP system implementation. Keywords: Enterprise Resource Planning, top management support, user involvement, education and training, successful implementation.